ND-SR-PB ISOTOPE SYSTEMATICS OF THE JURASSIC KASSANDRA-SITHONIA OPHIOLITES AND CHORTIATIS MAGMATIC ARC SUITE, EASTERN VARDAR ZONE, NE GREECE - Bonev, Nikolay; Chiaradia, Massimo (Ofioliti, 2024)
We report on the isotopic compositions of the intermediate rocks from Middle-Late Jurassic Chortiatis arc (160-173 Ma) and Kassandra-Sithonia back-arc ophiolites of Late Jurassic age (150-160 Ma), both exposed in the eastern Vardar Zone-western Circum-Rhodope belt transect of northeastern Greece. The Kassandra-Sithonia ophiolites consist of dunites, gabbros, basalts, and rhyolites, whose Nd-Sr-Pb isotopes are compatible with a dominant mantle-derived MORB component mixed with a detectable amount of crustal material and/or sediment entrained in their mantle source in a subduction zone. Their isotopic features are consistent with the origin of the studied rocks within the coupled Chortiatis arc/Kassandra-Sithonia back-arc system outboard the Eurasian continental margin (Serbo-Macedonian Massif). In both elements of the above-mentioned system, the documented Nd-Sr-Pb isotopes are comparable to those from the Middle Jurassic arc-related Evros ophiolite rocks (164-176 Ma) in the eastern Circum-Rhodope belt of Bulgaria and Greece. This implies the presence of regionwide Vardarian Jurassic arc/back-arc systems connected with both western and the eastern Circum-Rhodope belts. A rhyolite dated at 149 Ma that intrudes the Sithonia ophiolite displays distinct Nd-Sr-Pb isotopic features suggesting an origin connected to a subsequent Late Jurassic-Early Cretaceous north-directed flat subduction zone within the Kassandra-Sithonia back-arc region, beneath the Eurasian continental margin. This subduction zone explains the granitoid magmatism (138-155 Ma) recorded at that margin to the north.